PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEKERJA PROYEK DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI PADA PT JASA KONSTRUKSI BANJARNEGARA - Zidan Febriansyah; Hermin Endratno; Tri Septin Muji Rahayu; Purnadi (JURNAL ILMIAH EDUNOMIKA, 2026)
Project worker performance is a crucial factor determining a construction company's success in meeting quality, cost, and schedule targets. This study aims to analyze the impact of work motivation and work discipline on project worker performance, with job satisfaction serving as a mediating variable, at PT Jasa Konstruksi Banjarnegara. A quantitative approach was employed, utilizing a survey method involving 212 project workers selected through purposive sampling. Data were collected via questionnaires and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 3. The results indicate that work motivation and work discipline have a positive and significant effect on project worker performance. Furthermore, work motivation and work discipline positively and significantly influence job satisfaction, while job satisfaction has a positive and significant impact on worker performance. Mediation analysis reveals that job satisfaction significantly mediates the effects of work motivation and work discipline on project worker performance. These findings suggest that enhancing work motivation and discipline—supported by job satisfaction—can serve as an effective strategy to improve project worker performance within construction companies. Unlike previous studies, this research examines the mediating role of job satisfaction among daily-wage construction workers, whose roles are characterized by high-risk conditions and a focus on project targets.